Derivative Spectrophotometric Determination of Adapalene in its Bulk and Pharmaceutical Dosage Form - Adhikari, Lopamudra; Jagadev, Sarbeswar; Sahu, Sanjib; Moitra, S.K.; Murthy, P.N. (Asian Journal of Chemistry, 2011)
A rapid, simple UV spectrophtometric method is developed for routine analysis of adapalene in quality control laboratory. Both bulk drug and pharmaceutical dosage form is validated by this method. From the solubility profile study, a specific solvent was selected methanol and acetonitrile (8:2), wavelength maxima of the drug was found to be 230.8 nm. Simultaneously a derivative spectrophotometric method was developed and validated. The lmax and lmin was recorded 236.8 and 222.7 nm respectively. In the proposed method, adapalene follows linearity in the concentration range 3-23 μg/mL with a correlation coefficient 0.9996. The method was validated statistically as per ICH guidelines and by recovery study. The standard deviation was 0.02431 and RSD was found to be 2.52 %, which is equivalent 2 % with excellence precision and accuracy.